Technology Entrepreneurship Project (ENT 600) : Sony Corporation / Noor Syzwani Sulaiman - Sulaiman, Noor Syzwani (2021)
Sony is a company that strives to be the best. Our corporate strategy is to market and market creative and high-quality electronic consumer goods. As part of the company 's ongoing mission to consistently provide the industry's best dealer support, Sony Malaysia is launching its new Sony Designated Store Program to help distributors provide a better level of visual merchandising and customer services, while at the same time reducing distributor costs. One of products that produce by this company is Xperia 1 II. The product has two type which is Xperia 1 and Xperia 1 II. The purpose of this case study is to identify, analyse and investigate the company-based product, the problems of the product and proposed solutions to solve the problems. After doing the product analyses the latest Sony Xperia 1 ii does not meet the tastes of customers. The problem are sony Xperia 1 ii camera does not have a wide angle camera in the camera software. this becomes a problem that needs to be solved to help customers who are interested in photography. Indirectly, consumers buy Xperia 1 II phone because it is more about photography. In fact, the front camera of Sony Xperia 1 II does not have a wide angle. This can cause a significant problem because the Sony Xperia 1 II is for photography. This study come out the best solution in the problem. The best solution is make an innovation for wide angle front camera by making a small lens device. In this situation, there are two types of users that are not interested in front angle and like wide angle. This is because, the wide angle front camera also plays an important role in seeing the wide front situation.